Resposta :
Explicação passo-a-passo:
a) - 3x + 4 = 0
- 3x = 0-4
- 3x = -4
x = -4 ÷ -3
x = 1,3
b) 10 + x = 0
x = 0 -10
x = -10
c) x + 12 = 2x
x -2x = -12
-x = -12
x = 12
d) - 2x + 24 = 0
- 2x = 0 - 24
- 2x = -24
x = -24 ÷ -2
x = +12
e) x +1 = 0
x = 0 - 1
x = -1
f) - 20 + 5x = 0
+ 5x = 0 +20
+ 5x = +20
x = +20 ÷ +5
x = 4
g) 3x - 3 = 0
3x = 0 +3
3x = 3
x = 3÷3
x = 1
h) 4x - 2 = 0
4x = 0 +2
4x = 2
x = 2 ÷ 4
x = 0,5
Resposta:
Explicação passo a passo:
F= -20 +5x = 0
5x = 0 + 20
x = 20/5
x = 4
G = 3x - 3 = 0
3x = 0 + 3
x = 3/3
x = 1
H= 4x -2 = 0
4x = 0 + 2
x = 4/2
x = 2
![Ver imagem MANIITOWX](https://pt-static.z-dn.net/files/d13/2fd1bf9c2a49330bac9eeb88c4197c78.png)
![Ver imagem MANIITOWX](https://pt-static.z-dn.net/files/de5/4d3e4fc6e23bc5241a6a6dd660e0f81a.png)
![Ver imagem MANIITOWX](https://pt-static.z-dn.net/files/da7/7f6a5b0be549d7169fa39f315578087d.png)
![Ver imagem MANIITOWX](https://pt-static.z-dn.net/files/da6/a34a6e0ac65bb60747fe8700514c8a20.png)
![Ver imagem MANIITOWX](https://pt-static.z-dn.net/files/def/e9be754264ab5f6f1d9311916457c50e.png)